Digital Citizenship Skills of Undergraduate Students - Thuntuch Viphatphumiprathes (Journal of Humanities and Social Sciences Mahasarakham University, 2024)
The aims of this research were to study the digital citizenship skills of undergraduate students and to examine the factors affecting their digital citizenship skills. Data were collected in semester 2/2022 using a questionnaire, for which the IOC was 0.66-1.00, and Cronbach’s Alpha coefficient was 0.972. The sample group comprised 142 undergraduate students selected with the proportional stratified sampling method. The G*Power Program was utilized to calculate the size of the sample group. Mean, standard deviation, and multiple regression analysis with the stepwise method were used to analyze the collected data. The research results illustrated that the overall digital citizenship skills of undergraduate students were at a high level (= 3.75, SD =.66). When considered by aspect, analytical thinking was at the highest level (= 3.97, SD =.77), whereas personal information protection was at the lowest level (= 3.60, SD =.76). In addition, the factors affecting the digital citizenship skills of undergraduate students with a statistical significance of 0.05 included attitudes toward the internet and social media (X4), perceived self-efficacy with regard to computers and the in-ternet (X3), and learning achievement (X2). All three of these factors predicted the digital citizen-ship skills of undergraduate students at 58.1%. The prediction equation was =.478 +.383(X4) +.346(X3) +.142(X2).